A Case of Laparoscopic Sacrohysteropexy: A Uterus Preserving Surgical Procedure for the Treatment of Uterine Prolapse - Özge Senem Yücel; İlker Selçuk; Aslıhan Yazıcıoğlu; Gökhan Boyraz; Gürkan Bozdağ; İbrahim Esinler (Medical Network, 2016)
Pelvic organ prolapse (POP) is defined as the descent of pelvic organs from normal position due to pelvic floor dysfunction. A woman has a 11% life time risk of undergoing surgery for POP. A case of laparoscopic sacrohysteropexy, a uterus preserving surgical procedure for the treatment of uterine prolapse is presented and 6 month follow up outcomes are reported. A 26 year-old woman presented with complaints of a mass bulging out of her vagina and pressure feeling in her pelvis. Her pelvic examination revealed second degree uterine prolapse with no prolapse of anterior and posterior vaginal walls. She underwent laparoscopic sacrohysteropexy. On her follow up at first and sixth months postoperatively, she had remained asymptomatic. Her pelvic examination revealed no uterine prolapse. Laparoscopic sacrohysteropexy is an effective, safe and conservative procedure for the treatment of uterine prolapse.